Study Habits, Test Anxiety, and Learning Outcome of Students with Special Needs - Oseni, Isiaka Abiola; Bolaji, Yetunde Olanike; Adebowale, Adetola Alaba (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: This study investigated perceived relationships between study habits, test anxiety, and learning outcome among students with special needs at the Federal College of Education (Special) in Oyo, Nigeria. The study used correlational research design, which is ex-post facto in nature. Random sampling technique was used to select 264 participants for the study. Two validated and reliable instruments were adopted for data collection, namely TAI (Test Attitude Inventory) with r = .85 and SHC (Study Habits Checklist) with r = .61 were adopted to collect data for the study. Four hypotheses were formulated and tested at 0.05 significance level. Findings revealed that study habits and learning outcome of students with special needs are positively and significantly related (r = .380; df = 262; P < .05); while negative but significant relationship was found between test anxiety and learning outcome (r = -.480; df = 262; P < .05). Also, there were significant differences in study habits (t = 2.4201; df = 262; P < .05) and test anxiety (t = 1.860; df = 262; P < .05) between male and female (t = 2.4201; df = 262; P < .05). It was, therefore, recommended among others that study skills training should be incorporated into the school curriculum of the Nigeriaâs National Certificate in Education Programme. Also that students with special needs be encouraged and motivated to inculcate good study habits in their programme.Â KEYS WORD: Study Habits; Test Anxiety; Students with Special Needs; Learning Performance; College of Education Special.Â RESUME: âKebiasaan Belajar, Uji Kecemasan, dan Hasil Belajar Mahasiswa Berkebutuhan Khususâ. Penelitian ini mengkaji hubungan yang dirasakan antara kebiasaan belajar, uji kecemasan, dan hasil belajar mahasiswa berkebutuhan khusus di Sekolah Tinggi Pendidikan Khusus di Negara Bagian Oyo, Nigeria. Kajian menggunakan desain penelitian korelasional, yang merupakan âex-post factoâ secara alamiah. Teknik sampel acak digunakan untuk memilih 264 peserta dalam penelitian ini. Dua instrumen divalidasi dan dapat diandalkan, yakni ITS (Inventori Test Sikap) dengan r = 0.85 dan PKB (Pengecekan Kebiasaan Belajar) dengan r = 0.61, yang diadopsi untuk mengumpulkan data penelitian. Empat hipotesis dirumuskan dan diuji dengan tingkat signifikansi 0.05. Temuan penelitian mengungkapkan bahwa kebiasaan belajar dan hasil belajar mahasiswa berkebutuhan khusus memiliki hubungan positif dan signifikan (r = 0.380; df = 262; P < 0.05); sementara hubungan negatif tetapi signifikan ditemukan antara uji kecemasan dan hasil belajar (r = -.480; df = 262; P < 0,05). Juga ada perbedaan yang signifikan dalam kebiasaan belajar (t = 2.4201; df = 262; P < 0.05) dan uji kecemasan (t = 1.860; df = 262; P < 0.05) antara laki-laki dan perempuan (t = 2.4201; df = 262; P < 0.05). Oleh karena itu dianjurkan, antara lain, latihan keterampilan belajar harus dimasukkan kedalam kurikulum sekolah dalam Program Pendidikan Bersertifikat Nasional di Nigeria. Juga para mahasiswa berkebutuhan khusus harus didorong dan dimotivasi untuk menanamkan kebiasaan belajar yang baik dalam program mereka.KATA KUNCI: Kebiasaan Belajar; Uji Kecemasan; Mahasiswa Berkebutuhan Khusus; Hasil Belajar; Sekolah Tinggi Pendidikan Khusus.Â Â Â Â About the Authors: Isiaka Abiola Oseni, Yetunde Olanike Bolaji and Adetola Alaba Adebowale are the Lecturers at theÂ School of Special Education, Federal College of Education [Special], Oyo P.M.B. 1089, Oyo State, Nigeria. For academic interests, the authors can be contacted via their e-mails at: osenibiola@gmail.com and bolajiyetundeolanike@gmail.comHow to cite this article? Oseni, Isiaka Abiola, Yetunde Olanike Bolaji & Adetola Alaba Adebowale. (2016). âStudy Habits, Test Anxiety, and Learning Outcome of Students with Special Needsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(2) November, pp.205-212. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (June 20, 2016); Revised (September 19, 2016); and Published (November 30, 2016).